Impact Of Fragrant Pandan Leaves Ethanol Extract (Fplee) On Alt And Ast Levels In High-Fat Diet-Induced Rat - Sukanty, Ni Made Wiasty; Ariani, Farida; Yunita, Lina (Jurnal Riset Kesehatan, 2024)
Energy-dense, low-nutrient, and ultra-processed diets rich in fat can be a risk factor for fatty liver disease. Fragrant pandan is a plant that grows widely in Indonesia and is widely used as a herbal plant. This study aimed to determine the potential of fragrant pandan leaf ethanol extract (FPLEE) to reduce ALT and AST levels. It is a posttest control group design experiment. A total of 24 Rattus norvegicus specimens. All groups were given high-fat food for two weeks, except for NC. In the next two weeks, S was induced by simvastatin and FPLEE; T1, T2, and T3 were induced by 8, 16, and 32 mg/200 g BW/day, respectively. The One-Way ANOVA test results showed Î±=0.000 for ALT and Î±=0.029 for AST. Post-hoc LSD showed that NC was significantly different from T1, T2, and T3 (p<0.05); therefore, FPLEE was unable to reduce ALT levels. For AST levels, NC was significantly different from C+, T1, and T2 (P<0.05). Thus, T3 (32 mg/200 g BW/day of FPLEE) yielded the best results in reducing AST levels (p>0.05). Based on these results, FPLEE has side effects on liver function, as seen in increased blood ALT levels, but it can reduce blood AST levels.